Accurate Location of Catheter Tip With the Free-to-Total Metanephrine Ratio During Adrenal Vein Sampling - Christou, Foteini; Pivin, Edward; Denys, Alban; Abid, Karim A.; Zingg, Tobias; Matter, Maurice; Pechère-Bertschi, Antoinette; Maillard, Marc; Grouzmann, Eric; Wuerzner, Gregoire (Frontiers in Endocrinology, 2022)
Background The selectivity index (SI) of cortisol is used to document correct catheter placement during adrenal vein sampling (AVS) in patients with primary aldosteronism (PA). We aimed to determine the cutoff values of the selectivity indexes based on cortisol and free metanephrine using an adapted AVS sampling protocol in combination with computed tomography. Methods Adults with PA and referred for AVS were recruited in two hypertension centers. The cortisol-derived and free metaneprhine selective indexes were calculated as the concentration of the analyte in adrenal veins divided by that in distal vena cava. The free to total metanephrine ratio (FTMR)-derived SI was calculated as the concentration of free metanephrine in adrenal vein divided by that of total metanephrine in ipsilateral adrenal vein. The AVS was classified as an unequivocal radiological success (uAVS) if the tip of the catheter was in the adrenal vein. The SI cutoffs of each index marker were established using receiver operating characteristic curve analysis. Results Out of 125 enrolled patients, 65 patients had an uAVS. The determined cutoffs were respectively 2.6 for cortisol, 10.0 for free metanephrine, 0.31 for FTMR on the left side and 2.5, 9.9 and 0.25 on the right side. Compared to free metanephrine and the FTMR, cortisol misclassified AVS as unsuccessful in 36.6% and 39% of the cases. Conclusion This study is the first to determine the cutoffs of cortisol and free metanephrine selectivity indexes during AVS. It confirms that free metanephrine-based selectivity indexes are better than those based on cortisol.